2016
DOI: 10.3390/ijms17111857
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Protein Interaction Network Associated with Azoospermia

Abstract: Non-obstructive azoospermia is a severe infertility factor. Currently, the etiology of this condition remains elusive with several possible molecular pathway disruptions identified in the post-meiotic spermatozoa. In the presented study, in order to identify all possible candidate genes associated with azoospermia and to map their relationship, we present the first protein-protein interaction network related to azoospermia and analyze the complex effects of the related genes systematically. Using Online Mendel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Apart from obvious GO terms for broad biological processes, such as spermatogenesis, spermatid development, etc, many other specific terms were also found to be enriched among the 3,000 down-regulated genes in the current study, which have also been reported earlier to be key processes associated with NOA (e.g., 11,43,44). Though there were many common observations among the functions and pathways over-represented among genes up-or down-regulated as per earlier studies, a few new observations were also noted.…”
Section: Discussionsupporting
confidence: 78%
“…Apart from obvious GO terms for broad biological processes, such as spermatogenesis, spermatid development, etc, many other specific terms were also found to be enriched among the 3,000 down-regulated genes in the current study, which have also been reported earlier to be key processes associated with NOA (e.g., 11,43,44). Though there were many common observations among the functions and pathways over-represented among genes up-or down-regulated as per earlier studies, a few new observations were also noted.…”
Section: Discussionsupporting
confidence: 78%
“…The CREBBP (CREB-binding protein) gene is related to transcriptional coactivation of different transcription factors and has been associated with azoospermia (Sabetian & Shamsir, 2016). Partial disruption of CREBBP gene in mice interferes in germ cell development at the spermatocyte stage (Hummler et al, 1994) because CREB-binding protein is required to produce a critical Sertoli cell-derived factor for germ cell survival (Scobey et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The FDR (false discovery rate) was set as <1% on both protein and peptide levels. The data were normalized across the conditions including the replicates using spectral counts method 40,41 . For identifying differentially expressed proteins, the normalized peptide matches of the treatment were divided by that of control conditions.…”
Section: Methodsmentioning
confidence: 99%
“…PPI information of proteins was obtained from the String database (version 9.1; http://string-db.org/) having the confidence score > 0.7. It was further imported in Cytoscape (version 3.6.0; http://www.cytoscape.org/) and the union calculation was performed, followed by removal of the duplicated edges by using Advanced Network Merge 40,42 .…”
Section: Methodsmentioning
confidence: 99%